Radicalism in the South since Reconstruction - Green, Chris, 1968-; Rubin, Rachel, 1964-; Smethurst, James Edward (Palgrave Macmillan, 2007)
Framing the scholarly conversation about southern radicalism, this book features essays covering a range of historical periods and topics in dialogue with each other so as to get a sense of the range of southern politics and history.